A practical multi-objective optimization sectorization method for water distribution network - Zhang, Kui; Yan, Hexiang; Zeng, Han; Xin, Kunlun; Tao, Tao (The Science of the total environment, 2019)
In recent years, water leakage problems in water distribution networks (WDN) have been attracting more attention, with an emphasis on energy and water resources. As one of the measures used for flow monitoring and leakage control, water network sectorization is a research hotspot in China. This paper, which begins with an introduction of present sectorization methods, proposes a multi-objective optimization sectorization method based on a comprehensive consideration of the hydraulics, water quality and economy. This method is based on the non-dominated sorting genetic algorithm (NSGA-II) which is a heuristic algorithm for multi-objective optimization to obtain the optimal schemes. In addition, human experience is also considered in the optimization process. In a case study, this method proves to be efficient in producing good results with little impact on the hydraulics and water quality of the WDN, and the results obtained are acceptable for multiple objectives. Therefore, this method provides references for the transformation of future water distribution network sectorization. [Display omitted] •Water leakage problem caused a large quantity of water loss and it needs to be solved urgently.•Water network sectorization are beneficial for the control of water leakage through flow monitoring and management.•We applied Non-dominated sorting genetic algorithm-II (NSGA-II) in water network sectorization.•Natural and administrative boundaries were considered when defining the main pipes.•The connecting pipes were partially optimized to improve the hydraulic links and water quality.